Modeling of an all-vanadium redox flow battery and optimization of flow rates - Li Jinbin. (2013)
Vanadium redox flow batteries (VRBs) are competitive for large energy storage systems due to low manufacture and maintenance costs and high design flexibility. Electrolyte flow rates have significant influence on the performance and efficiencies of the batteries. High electrolyte flow rates improve energy efficiency while degrade the battery efficiency due to high pump power losses. Thus, flow rates are necessary to be optimized for battery efficiency improvement. In this paper, an electrochemical model is firstly proposed to describe the charge-discharge characteristics based on the experimental data. Then, an empirical method is introduced to analyze the energy consumption of pumps under various flow rates. The optimal flow rates are obtained by applying new criteria. The results show that VRBs obtain peak battery efficiencies at the optimal flow rates around 90cm3s−1 with respect to the proposed battery configuration. The optimal flow rates are provided as a reference for battery operations and control.